1998
DOI: 10.1093/humrep/13.suppl_4.11
|View full text |Cite
|
Sign up to set email alerts
|

Sperm nuclear DNA damage and altered chromatin structure: effect on fertilization and embryo development

Abstract: In the first part of this report we investigate whether chromatin anomalies in human spermatozoa can influence fertilization after intracytoplasmic sperm injection (ICSI). We have examined the sperm chromatin packaging quality using the chromomycin A3 (CMA3) fluorochrome and the presence of DNA damage in spermatozoa using in-situ nick translation. When comparing the spermatozoa of patients undergoing in-vitro fertilization (IVF) and ICSI distinct differences are evident in that ICSI males have a higher CMA3 fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(104 citation statements)
references
References 37 publications
2
97
0
5
Order By: Relevance
“…In some studies, CMA3 fluorochrome has been used to evaluate the sperm quality and fertilization capacity. Sakkas et al [27] found that men who had a high percentage of anomalies in their chromatin, i.e. >30% CMA3 fluorescence and >10% nicks, had more than double the number of unfertilized oocytes containing spermatozoa that had remained condensed.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, CMA3 fluorochrome has been used to evaluate the sperm quality and fertilization capacity. Sakkas et al [27] found that men who had a high percentage of anomalies in their chromatin, i.e. >30% CMA3 fluorescence and >10% nicks, had more than double the number of unfertilized oocytes containing spermatozoa that had remained condensed.…”
Section: Discussionmentioning
confidence: 99%
“…In this connection, it must be remembered that several studies have demonstrated that a variable but consistent fraction of human spermatozoa exhibits abnormalities in chromatin structure, not always detected using classical parameters of evaluation (12)(13)(14)(15)(16)(17)(18)(33)(34)(35). Moreover the existence of a close relationship between chromatin and DNA structural abnormalities and male infertility has been well pointed out.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, a number of studies have shown that variable but consistent fractions of human spermatozoa not always detectable on the basis of classic morphological parameters, contain serious chromatin structural abnormalities and DNA strand breaks (12)(13)(14)(15)(16)(17)(18). The existence of an association between sperm chromatin malformation and male infertility has been repeatedly observed in humans and structural chromatin abnormalities have been found to exert negative effects both on the percentage of fertilization and on embryonic development (17,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…In all the studies, adverse effects on conventional sperm parameters and DNA integrity were documented (Karabinus et al, 1997). There is evidence that sperm with an impaired DNA integrity is capable of fertilizing oocytes, but the subsequent embryonic development is impaired (Sakkas et al, 1998;Larson et al, 2000). Setchell (1998) reported a decrease in fertilization rate of sheep ova obtained from abattoir and fertilized with sperm from scrotal-insulated rams.…”
Section: Effects Of Hyperthermia On Dna Integrity and Embryonic Develmentioning
confidence: 99%